Five new taxa and a new record of Euastrum (Desmidiaceae) from the Chapada Diamantina region, Bahia State, Brazil - Costa, Fabiana De Matos; Ramos, Geraldo José Peixoto; Oliveira, Ivania Batista; Bicudo, Carlos Eduardo De Mattos; Moura, Carlos Wallace Do Nascimento (Phytotaxa, 2018)
We describe five new taxa of Euastrum (E. abruptum var. chapadae, E. fissum var. nordestinum, E. marimbusense, E. ornatiscrobiculatum and E. praemorsum var. foersteri), and report a new record for the Northeastern Region of Brazil (E. groenbladii) from periphyton samples collected in the Pantanal dos Marimbus in the Chapada Diamantina, Bahia State, Brazil. Taxonomic notes and ecological characteristics of the taxa are provided.